An Organic Geochemical, Study to Compare Jurassic Black Shale-hosted Manganese Carbonate Deposits: Úrkút, Hungary, and Branisko Mountains, East Slovakia - Márta Polgári; Molák. Bohumil; Eva Surová (Canadian Institute of Mining, Metallurgy and Petroleum, 1992)
The Úrkút rhodochrosite deposit and Branisko Mn showings (rancieite, manganiferous calcite), located in Lower Jurassic marine sedimentary rocks with black shale, were studied by organicgeochemical methods. Both depositional localities were affected by the Lower Jurassic Toarcian anoxic event. UrkUt shales are rich in organic matter (av. 2.94 wtOJo total organic carbon), the composition of which indicates derivation mainly from marine sources, with some terrigenous component. The shales matured in a bacterially active environment under reducing conditions of diagenesis-catagenesis. Branisko shales (~0.2 wt % TOC) with lenses of Mn oxide ore were weakly metamorphosed and their organic matter thermally degraded. The model for Mn carbonate ore formation envisages reaction of Mn derived from sediments, with carbonate generated by a bacterially mediated process of decomposition of organic matter that also involved Mn reduction.